Desarrollo rural y envejecimiento : caso de estudio municipio de Chinavita, Boyacá, Colombia - López, Erica Paola; Martínez Gutiérrez, Lina Marcela; Martínez Cañas, Camilo Andrés; Vargas Prieto, Amanda (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 193-206).